A cross-sectional study of equol producer status and self-reported vasomotor symptoms. Issue 5 (May 2015) - Newton, Katherine M.; Reed, Susan D.; Uchiyama, Shigeto; Qu, Conghui; Ueno, Tomomi; Iwashita, Soh; Gunderson, Gabrielle; Fuller, Sharon; Lampe, Johanna W.
Abstract: Objective: This study aims to evaluate the associations of vasomotor symptom (VMS) frequency, bother, and severity with equol producer status and dietary daidzein intake. Methods: This is an observational study. This study included women aged 45 to 55 years, in postmenopause or in the menopausal transition, who had soy food intake of three or more servings per week. Exclusion criteria included severe concurrent disease, pregnancy or planned pregnancy, and current use of oral or transdermal hormones or selective estrogen receptor modulators. After screening, 375 participants completed a 3-day VMS diary and a 24-hour urine collection. Women with a urine daidzein or genistein concentration of 100 ng/mL or higher were included. We evaluated the association of VMS—dichotomized as lower than or equal to versus higher than the mean number of VMS per day (<2.33, ≥2.33)—with quartiles of daidzein intake. Results: Overall, 129 (35%) of 365 women were equol producers. The mean (SD) urinary equol excretion was 0.67 (1.57) mg/day (50th percentile, 0 mg/d; 95th percentile, 4.12 mg/d). Among equol producers, the mean (SD) urinary equol excretion was 1.91 (2.15) mg/day (50th percentile, 1.09 mg/d; 95th percentile, 6.27 mg/d). Among equol producers, compared with those in the lowest quartile of dietary daidzein intake (mean, 4.9 mg/d), those in the highest quartile (mean, 28.5 mg/d) were 76% less likely to have VMS higher than the mean number of VMS (odds ratio, 0.24; 95% CI, 0.07-0.83; trend test across all daidzein levels, P = 0.06). Among equol nonproducers, there were no associations between daidzein intake and VMS frequency. There were no differences in VMS bother or severity among equol producers or nonproducers by dietary daidzein level. Conclusions: Among equol producers, higher equol availability attributable to higher soy consumption contributes to decreased VMS.